Zakat Profesi (Zakat Penghasilan) Menurut Hukum Islam - Tira Nur Fitria (ITB AAS INDONESIA Surakarta, 2015)
This study aims to find out about the zakat profession (tithe income) in Islamic view (Islamic law). This research is qualitative descriptive. This study included literature to examine the written sources such as scientific journals, books referesni, literature, encyclopedias, scientific articles, scientific papers and other sources that are relevant and related to the object being studied. As for the object of study of this research is in the form of texts or writings that describe and explain about the profession zakat (tithe income). Results from this study is obligatory of Zakat profession together with the charity business and other income such as agriculture, livestock and trade. Limit nisab wealth derived from the business professions can be equated with charity nisab plant yield is 5 wasaq (about 750 kg of rice), with the obligation of zakat 5% or 10%, and is payable when earning achievements, rewards or wages of the profession. For kind of professions such as doctors in hospitals, teachers or lecturers who only received a fixed salary of the workings of government agencies, likened nisab nisabnya with gold and silver, which is 93.6 grams, with the obligation of zakat 2.5 percent, which is issued every one years, and having expended costs of basic necessities.Keywords: zakat profession / income zakat, Islamic lawÂ